TLR9 activation induces aberrant IgA glycosylation via APRIL- and IL-6-mediated pathways in IgA nephropathy - Makita, Yuko (Kidney Int, 2019)
Galactose-deficient IgA1 (Gd-IgA1) plays a crucial role in the development of IgA nephropathy (IgAN). However, the pathogenic mechanisms driving Gd-IgA1 production have not been fully elucidated. Innate-immune activation via Toll-like receptor 9 (TLR9) is known to be involved in Gd-IgA1 production. A proliferation-inducing ligand (APRIL) and IL-6 are also known to enhance Gd-IgA1 synthesis in IgAN. Here, we investigated how TLR9 activation in IgA-secreting cells results in overproduction of nephritogenic IgA in the IgAN-prone ddY mouse model and in human IgA1-secreting cells. Injection of CpG-ODN (TLR9 ligand) increased production of aberrantly glycosylated IgA and IgG-IgA immune complexes (IC) in ddY mice that, in turn, exacerbated kidney injury. CpG-ODN-stimulated mice had elevated serum levels of APRIL that correlated with those of aberrantly glycosylated IgA and IgG-IgA IC. In vitro, TLR9 activation enhanced production of the nephritogenic IgA as well as APRIL and IL-6 in splenocytes of ddY mice and in human IgA1-secreting cells. However, siRNA knock-down of APRIL completely suppressed overproduction of Gd-IgA1 induced by IL-6. Neutralization of IL-6 reduced CpG-ODN-induced overproduction of Gd-IgA1. Furthermore, APRIL and IL-6 pathways each independently mediated TLR9-induced overproduction of Gd-IgA1. In summary, TLR9 activation enhanced synthesis of aberrantly glycosylated IgA that, in a mouse model of IgAN, further enhanced kidney injury. These findings indicate that APRIL and IL-6 synergistically, as well as independently, enhance synthesis of Gd-IgA1.